Longrange PCR-based next-generation sequencing in pharmacokinetics and pharmacodynamics study of propofol among patients under general anaesthesia. Issue 1 (December 2017) - Zakerska-Banaszak, Oliwia; Skrzypczak-Zielinska, Marzena; Tamowicz, Barbara; Mikstacki, Adam; Walczak, Michal; Prendecki, Michal; Dorszewska, Jolanta; Pollak, Agnieszka; Lechowicz, Urszula; Oldak, Monika; Huminska-Lisowska, Kinga; Molinska-Glura, Marta; et al.
Abstract The individual response of patients to propofol results from the influence of genetic factors. However, the state of knowledge in this matter still remains insufficient. The aim of our study was to determine genetic predictors of variable pharmacokinetics and pharmacodynamics of propofol within selected 9 genes coding for propofol biotransformation enzymes, receptors and transporters. Our studies are the first extensive pharmaocgenetics research of propofol using high throughput sequencing technology. After the design and optimization of long range PCR-based next-generation sequencing experiment, we screened promoter and coding sequences of all genes analyzed among 87 Polish patients undergoing general anaesthesia with propofol. Initially we found that two variants, c.516 G > T in theCYP2B6 gene and c.2677 T > G in theABCB1 gene, significantly correlate with propofol's metabolic profile, however after Bonferroni correction the P-values were not statistically significant. Our results suggest, that variants within theCYP2B6 andABCB1 genes correlate stronger with propofol's metabolic profile compared to other 7 genes.CYP2B6 andABCB1 variants can play a potentially important role in response to this anaesthetic and they are promising object for further studies.